Analisis Hubungan Pengetahuan Ibu Tentang Gizi dengan Pertumbuhan Anak Balita di Gampong Manyang Kecamatan Meurah Mulia Kabupaten Aceh Utara - Srie Wahyuni; Quranayati Quranayati; Sita Dara Humaira (Jurnal Kesehatan Amanah, 2026)
The growth of children under five is an important indicator in assessing children’s health and nutritional status. One of the factors influencing the growth of under-five children is maternal knowledge of nutrition. Adequate maternal knowledge is expected to support the optimal fulfillment of children’s nutritional needs. This study aimed to analyze the relationship between maternal nutritional knowledge and the growth of under-five children in Gampong Manyang, Meurah Mulia Subdistrict, North Aceh Regency. This study employed an analytical design with a cross-sectional approach. The population consisted of all mothers with under-five children in Gampong Manyang, with a total sample of 30 respondents selected using total sampling/purposive sampling techniques. Maternal knowledge data were collected using a questionnaire, while data on children’s growth were obtained through measurements of body weight and height based on anthropometric indicators. Data analysis was conducted using the Chi-Square test. The results showed that the majority of mothers had good nutritional knowledge, totaling 15 respondents (50%), and most under-five children had normal growth, with 12 children (40%). Statistical analysis revealed a p-value of 0.018 (p < 0.05), indicating a significant relationship between maternal nutritional knowledge and the growth of under-five children. In conclusion, there is a significant relationship between maternal nutritional knowledge and the growth of under-five children in Gampong Manyang, Meurah Mulia Subdistrict, North Aceh Regency. It is recommended that health workers enhance nutrition education for mothers of under-five children to support optimal child growth.